2008
DOI: 10.1097/mco.0b013e3283023d37
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nutritional status on body functioning in chronic obstructive pulmonary disease and how to intervene

Abstract: Diet, as a modifiable risk factor, appears more as an option to prevent and modify the course of chronic obstructive pulmonary disease. Reduction of mechanical disadvantage, physical training and anabolic agents should be used conjointly with oral nutrition supplements to overcome undernutrition and might change the prognosis of the disease in some cases. Major research challenges address the role of systemic inflammation and the best interventions for controlling it besides smoking cessation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 84 publications
0
33
0
1
Order By: Relevance
“…The corollary of this finding is that measurement of serum albumin should not be used as a marker for underlying malnutrition. Malnutrition may occur in other chronic diseases, such as inflammatory bowel disease [66][67][68], rheumatoid arthritis [69][70][71][72][73][74][75][76], or chronic obstructive pulmonary disease [77][78][79][80][81]. Although we fear that physicians may rely on serum albumin to determine whether malnutrition is present, our data in SSc suggest that, as in other conditions, such as anorexia nervosa [34], elderly age [39], and end-stage renal disease [37,82,83], serum albumin may be well within the normal range in patients at high risk for malnutrition.…”
Section: Serum Albumin In Sclerodermamentioning
confidence: 99%
“…The corollary of this finding is that measurement of serum albumin should not be used as a marker for underlying malnutrition. Malnutrition may occur in other chronic diseases, such as inflammatory bowel disease [66][67][68], rheumatoid arthritis [69][70][71][72][73][74][75][76], or chronic obstructive pulmonary disease [77][78][79][80][81]. Although we fear that physicians may rely on serum albumin to determine whether malnutrition is present, our data in SSc suggest that, as in other conditions, such as anorexia nervosa [34], elderly age [39], and end-stage renal disease [37,82,83], serum albumin may be well within the normal range in patients at high risk for malnutrition.…”
Section: Serum Albumin In Sclerodermamentioning
confidence: 99%
“…Its prevalence ranges from 20 to 40% in out-patients and up to 70% in patients with acute respiratory failure or waiting for lung transplantation. 20 Malnutrition is associated with deterioration of physical performance and development of clinical complications. Survival studies have shown significantly higher mortality rates in underweight patients than in overweight patients affected by COPD.…”
Section: Introductionmentioning
confidence: 99%
“…In adults with chronic respiratory failure requiring mechanical ventilation, undernutrition has been associated with the loss of inspiratory, expiratory, and diaphragmatic muscles resulting in increased respiratory effort, infectious risk, and decreased physical conditioning. 8,9,34 The increased respiratory effort leads to an increase in energy demand, further contributing to the nutrient imbalance and nutritional state. Careful monitoring and guided interventions to optimize nutrition status are critical in this cohort.…”
Section: Discussionmentioning
confidence: 99%